Globalization, structural change and interregional productivity growth in the emerging countries - Jagannath Mallick (Asian Development Bank Institute (ADBI), 2017)
The aim of this paper is to contribute to the debate on the structural change effects or labor reallocation effects on the regional disparity in productivity growth in India and the People's Republic of China (PRC). The paper uses secondary data at the state level in India and provinces in the PRC between 1993 and 2010. This paper uses the generalized method of moment (GMM) system estimator in a dynamic spatial panel data framework for the empirical analysis. The empirical investigations draw four results. First, the shift-share analysis suggests that the low-income regions have a higher structural change effect on labor productivity growth (LPG) than the high-income and middle-income regions. Second, the structural change has played an important role in boosting LPG. Third, the neighborhood effects also contribute positively to LPG. Fourth, human capital, investment in fixed assets, and FDI have boosted LPG. Finally, I suggest that policymakers should consider the role of structural change effects along with the neighborhood relationship, human capital, physical investment, and FDI for designing policies in order to reduce disparities in productivity growth, and hence economic growth, which will in turn help to avoid the middle-income trap.
Keywords: F02; F43; R11; L1; 330; globalization; structural change; regional productivity growth; dynamic spatial panel